2014
DOI: 10.1007/s00455-014-9577-y
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased Tongue Pressure is Associated with Sarcopenia and Sarcopenic Dysphagia in the Elderly

Abstract: The aim of this study was to clarify the association between tongue pressure and factors related to sarcopenia such as aging, activities of daily living, nutritional state, and dysphagia. One-hundred-and-four patients without a history of treatment of stroke and without a diagnosis of neurodegenerative disease (36 men and 68 women), with a mean age of 84.1 ± 5.6 years, hospitalized from May 2013 to June 2013 were included in this study. Maximum voluntary tongue pressure against the palate (MTP) was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
176
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(198 citation statements)
references
References 41 publications
(66 reference statements)
10
176
4
2
Order By: Relevance
“…CC measures not only muscle mass but also bone, subcutaneous adipose, and skin. It is not surprising that the cut-off values in this study were lower because compared with healthy adults, hospitalized patients tend to have an increased malnutrition risk [10,17,18,19] and elderly patients are likely to have thin subcutaneous adipose layers and skin. Therefore, we propose that the CC cut-off values determined in this study would be most useful clinically in hospitalized elderly patients.…”
Section: Discussionmentioning
confidence: 93%
“…CC measures not only muscle mass but also bone, subcutaneous adipose, and skin. It is not surprising that the cut-off values in this study were lower because compared with healthy adults, hospitalized patients tend to have an increased malnutrition risk [10,17,18,19] and elderly patients are likely to have thin subcutaneous adipose layers and skin. Therefore, we propose that the CC cut-off values determined in this study would be most useful clinically in hospitalized elderly patients.…”
Section: Discussionmentioning
confidence: 93%
“…These latter scale levels consider both diet modifications and patient compensations [9]. Clinically significant dysphagia was defined as requirement for modification of an oral diet (FOIS grades 1–5) [7, 10]. According to previous studies, dysphagia was defined as having a FOIS level of 5 or less in the present study [7, 10].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a recent investigation demonstrated that dysphagia was related to sarcopenia or the causes of sarcopenia in hospitalized elderly patients without a history of treatment for stroke, and without diagnosis of neurodegenerative disease [7]. CHF patients with cardiac cachexia, caused by malnutrition, have mortality 2–3 times higher compared with non-cachectic CHF patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…So beeinträchtigt der im Alter zu beobachtende Muskelabbau, die Sarkopenie, generell die motorische Komponente des Schluckens [8]. Zudem wird der Schluckakt durch Veränderungen des Bindegewebes, das im Alter an Elastizität verliert, modifiziert [9].…”
Section: Primäre Und Sekundäre Presbyphagieunclassified
“…Dieser Begriff wird definiert als ungewollter Verlust von Skelettmuskelmasse und daraus resultierend auch der Muskelstärke [27]. Grundsätzlich scheinen Patienten mit einer Sarkopenie häufiger eine Beeinträchti-gung des Schluckaktes aufzuweisen [8]. Es finden sich Hinweise darauf, dass die Schluckmuskulatur bei diesen Patienten von der Sarkopenie mit erfasst wird und so zu einer Verschlechterung der Schluckfunktion beiträgt.…”
Section: Sarkopenieunclassified